Relações de aprendizagem em ambiente virtual imersivo para a formação de operadores no setor elétrico - Mancia, Letícia Beraldi (2019)
This research aimed to investigate the effectiveness of a learning environment mediated by virtual reality technology. This virtual environment was developed to be part of the initial and ongoing training of electrician operators working in the electric sector, specifically in Copel Geração e Transmissão S/A. The methodology consisted of three stages: a)First of all, in the development of a Learning Guide based on the theories of Robert Gagné and Gamification to perform an immersive virtual maintenance activity; b) Three moments of interventions, where the operators could experience the environment and virtual reality through the technology execution of the proposed virtual maintenance activity and; c) Interviews with the participants of the activities. Through the phenomenological analysis of interviews and users' immersion logs, significant results were obtained regarding learning in this environment, making it possible to identify and categorize relationships and learning processes according to the theoretical framework used. The results demonstrated that the environment produces learning relationships in its users and is capable of creating and improving the skills and competencies required for the electric sector. This dissertation is part of the Postgraduate Program in Technology (PPGTE) of the Federal Technological University of Paraná (UTFPR) and a Research and Development Project (R & D - ANEEL 6491-0299 / 2013) - RV2: Virtual Reality Technology, Tangible Interaction, Computer Models and Perversive Simulation Applied to the Maintenance Training of Live Lines.